Leadership characteristics and their relationship to self-confidence among kindergarten children Research (Journal of the College of Basic Education, 2025)
The current research aims to identify the level of leadership characteristics among kindergarten children and their relationship to their self-confidence, as the research sample consisted of (40) children who were selected randomly and their teachers were consulted to answer the scale. To achieve the research objectives, the researcher used two scales: the first: leadership characteristics, which consists of (40) paragraphs, and the self-confidence scale, which consists of (40) paragraphs. After the researcher verified their validity and reliability, the two scales were applied to the individuals of the research sample. After collecting and statistically analyzing the data, the researcher reached the following results:Kindergarten children in Baghdad enjoy an acceptable level of leadership characteristics and self-confidence.Children who have peers enjoy an acceptable level of leadership characteristics and self-confidence.Children who live in extended families enjoy leadership characteristics and self-confidence more than children who live in nuclear families. In light of the research results, the researcher came up with a number of recommendations, including:Holding seminars in kindergartens in the six Baghdad directorates on ways to enhance and increase children's self-confidence.Enriching the child's environment by providing the necessary supplies of games, educational activities, and programs that develop leadership characteristics.The need to pay attention to everyone who helps develop leadership characteristics and self-confidence among kindergarten children.The need to pay attention to children who lost their parents or one of their family members as a result of the circumstances that Iraq went through.